تطوير مادة كتاب المتممة الأجرومية على أساس خريطة المفاهيم لترقية كفاءة الطالبات في علم النحو بمعهد سبيل الرشاد السلفى مالانج - Diana, Zahara Ulya; Jauhari, Qomi' Akit (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
ABSTRACT Not Nahwu material is the ultimate goal in learning, but requires media in achieving goals. Media in learning is very important for the students in Nahwu material. In order for teachers to deliver Nahwu material attractively and effectively, media is needed. Researchers take one of the media that is in accordance with this study, namely the concept of thinking (concept map). The formulation of the problem in this study is: (1) How is the development of the book Mutamminah Al-Ajrumiyah complementary to nahwu subjects based on the, concept map at the Diniyyah level at the Sabilurrasyad Salafi Malang Islamic Boarding School? (2) How effective is the use of textbooks for, concept map based Nahwu material at the early level at the Sabilurrasyad Salafi Malang Islamic Boarding School? This research uses Research and Development method. The development model used is the ADDIE model which has 5 stages of research and development. The data collection techniques used are tests (pretest and post test), interviews, test questionnaires of validators of media experts and material experts, and user response questionnaires. Meanwhile, to analyze data related to the effectiveness of the use of electronic modules, researchers use the N-Gain formula. The results shows: (1) the development of the book Mutamamah al-Ajrumiyah then developed into the "Practical Book of Nahwu", in accordance with the material. (2) The result of the validation value of book and language method experts is 88% and the result of media expert validation value is 94%. Based on these data, it is known that this book can be done by students from the value of the N-Gain calculation results. The level of effectiveness of the book produces an N-value of 65.5 or a percentage of 65% that the mind map is effective. ملخص ليس مادة النحو الأهدف الآخر في التدريس ولكن يحتاج الوسيلة لتحقيق الأهداف، هذه وسيلة أمر مهم للتلاميذ عند مادة النحو لكي يستطيع مدرسة أن يعرض المواد باجاذبة والفعالية فاحتاج الوسيلة. تأخذ الباحثة إحدى الوسائل المناسبة لهذا البحث وهي الخريطة الذهنية. أما مشكلة البحث إلى الحصول على الوصف التطوري منها: (١) كيف تتم إجراءات تطوير الكتاب المتممة الآجرومية في مادة علم النحو على أساس الخريطة المفاهيم لمرحلة دينية بمعهد سبيل الرشاد السلفي مالانج, (2) كيف فعالية استخدام تطوير العملية التعليمية لمادة علم النحو على الخريطة المفاهيم لمرحلة دينية معهد سبيل الرشاد السلفي مالانج. يستخدم هذا البحث طريقة البحث والتطوير. نموذج التطوير المستخدم هو نموذج ADDIE الذي يحتوي على خمسة مراحل من البحث والتطوير. تقنيات جمع البيانات المستخدمة هي الاختبارات (الاختبار القبلي والاختبار البعدي)، والمقابلات، واستبيانات الاختبار لمدققي خبراء الإعلام وخبراء المواد، واستبيانات استجابة المستخدم. وفي الوقت نفسه، لتحليل البيانات المتعلقة بفعالية استخدام الوحدات الإلكترونية، يستخدم الباحثة صيغة N-Gain. نتائج هذا البحث هي: (1) التطوير، أي من كتاب متممة الآجرومية ثم تطويرها إلى الكتاب مسير النحو سواء كان من المادة (2) تبلغ قيمة التحقق من صحة خبير الكتاب واللغة 88٪ ومن التحقق من صحة خبير الوسيلة 94%. بناء على هذه البيانات من المعروف أن هذه كتاب قابلة للتنفيذ للطالبات من قيمة نتيجة حساب N-Gain، ينتج معدل فعالية كتاب قيمة N تبلغ 65,5 أو نسبة مئوية قدرها 65٪ أن الخرائط المفاهيم فعالية.